Envelhecimento humano : ações motivadoras para a prática de exercícios físicos - Stefanello, Stela Maris Stefanello (2012)
To yearn for the human aging process with life quality, different actions are proposed not only the physical practice but self-care actions, essential in searching of a health old age. The main specific objective of this study aim to understand the subject in relation to the human aging, investigate the actions of self-care would identify the physical exercises incorporate its benefits obtained under the look of healthy human aging process. The sample certified in seven people with aged 45 to 59 years old, five females and 2 male, performers of physical exercises for over 3 years in a Gym A in a town called Ijuí. The research presented a descriptive character with qualitative approach. The collected data instrument certified the semi structure interview, which was recorded and written in totality, identifying the participants as people in alphabetic order and Italics letters, without modifying the data transcription and the anonymity. The data were collected during the month of February of 2011, following a schedule of appointments and locals with to the sample research peole. The categories to the analyses and discussions were formulated by a data collected and to a better development of chapters arguing were used among the authors related to the referencial theory, the saying of interviewers and the discussions of researchers. Reporting the following, the man action motivated from people in the continuity of practicing physical exercises. Distinguishing the actions of self care people, the following process: Keep a routine of physical exercises, preventive medicine, use sunscream, careand about aesthetics, keep a balanced food and appropriated sleep, enjoy the work and leisure moments. The physical exercises of muscular strengthen and cardio-respiratory, concomitantly with stretching exercises were incorporated by those persons in the study. The benefits obtained with these practices were obtained: reduction in the ostemuscular pains, to tone up the muscles and keeping the lean body mass, improvement of health and quality of life, helping the preventions to keep the autonomy in the old ages and also the delay of human aging process